Neotypification of Stomatanthes helenae (Buscal. & Muschl.) Lisowski (Asteraceae): The curious history of an African specimen - Grossi, Mariana Andrea (2011)
The holotype of the name of the Central African species Stomatanthes helenae (Buscal. & Muschl.) Lisowski (Asteraceae), initially described as Eupatorium helenae Buscal. & Muschl., was destroyed during the World War II. No other original material of this name was found, except for an illustration housed at BR. A specimen from BRLU herbarium is chosen here as neotype of Eupatorium helenae. Additionally, a re-description of the species, an illustration, a distribution map, as well as a key to the African species of Stomatanthes, are provided.